Mucosa-Associated Lymphoid Tissue Lymphoma of the Thyroid Gland: A Systematic Review of the Literature. Issue 1 (18th January 2020) - Karvounis, Evangelos; Kappas, Ioannis; Angelousi, Anna; Makris, Georgios-Marios; Kassi, Eva
Abstract : Objective: Extranodal marginal zone B-cell lymphoma of mucosa-associated lymphoid tissue (MALT) type of the thyroid gland is a rare indolent malignant disease encountered in approximately 0.5% of patients with Hashimoto thyroiditis (HT). The purpose of the present systematic review was to accumulate the current evidence in the field. Study Design: We searched the Medline, Scopus, EMBASE, ClinicalTrials.gov, and Cochrane Central Register of Controlled Trials CENTRAL databases from inception to May 2018. Statistical analysis was performed with SPSS version 22.0. Results: Fourteen case series and 20 case reports were finally included in the present systematic review. Analysis of the patient data included in the published case reports suggested that the age at diagnosis of MALT lymphoma does no differ among males and females (64 [52.5–73] vs. 67 [60.5–72] years, p = 0.442). HT was detected in 60% of patients, whereas coexisting carcinoma was evident in 17% of cases. The incidence of HT and thyroid cancer was comparable among males and females ( p = 0.474 and p > 0.999, respectively). Among all patients included in the present systematic review there were two disease relapses and two deaths attributed to the disease. Conclusion: MALT lymphoma of the thyroid gland is a rare malignancy with an indolent course. The scarce data available in the literature preclude safe conclusions concerning the mode of treatment and follow-up of these patients. However, the combination of minimally invasive surgery and adjuvant therapy seems feasible. Moreover, an extended follow-up period is recommended.